Use of immune repertoire sequencing to resolve discordant microscopic and immunochemical findings in a case of T cell-rich large B cell lymphoma in a young dog - Lee, Gary Kwok Cheong; Bienzle, Dorothee; Keller, Stefan Matthias; Hwang, Mei-Hua; Darzentas, Nikos; Chang, Haiyang; Rätsep, Emily; Egan, Rebecca; Beeler-Marfisi, Janet (BMC veterinary research, 2021)
BACKGROUND: Lymphocytic neoplasms with frequent reactive lymphocytes are uncommonly reported in dogs, and can pose a diagnostic challenge. Different diagnostic modalities such as cytology, flow cytometry, histopathology, immunohistochemistry, and clonality testing, are sometimes required for a diagnosis. This report illustrates the value of using a multi-modal diagnostic approach to decipher a complex lymphocytic tumor, and introduces immune repertoire sequencing as a diagnostic adjunct. CASE PRESENTATION: A 10-month-old Great Dane was referred for marked ascites. Cytologic analysis of abdominal fluid and hepatic aspirates revealed a mixed lymphocyte population including numerous large lymphocytes, yielding a diagnosis of lymphoma. Flow cytometrically, abdominal fluid lymphocytes were highly positive for CD4, CD5, CD18, CD45, and MHC II, consistent with T cell lymphoma. Due to a rapidly deteriorating clinical condition, the dog was euthanized. Post mortem histologic evaluation showed effacement of the liver by aggregates of B cells surrounded by T cells, suggestive of hepatic T cell-rich large B cell lymphoma. Immune repertoire sequencing confirmed the presence of clonal B cells in the liver but not the abdominal fluid, whereas reactive T cells with shared, polyclonal immune repertoires were found in both locations. CONCLUSIONS: T cell-rich large B cell lymphoma is a rare neoplasm in dogs that may be challenging to diagnose and classify due to mixed lymphocyte populations. In this case, the results of histopathology, immunohistochemistry and immune repertoire sequencing were most consistent with a hepatic B cell neoplasm and reactive T cells exfoliating into the abdominal fluid. Immune repertoire sequencing was helpful in delineating neoplastic from reactive lymphocytes and characterizing repertoire overlap in both compartments. The potential pitfalls of equating atypical cytomorphology and monotypic marker expression in neoplasia are highlighted.
Keywords: difúzní velkobuněčný B-lymfom; Liver; Liver Neoplasms; ascites; podskupiny lymfocytů; T-Lymphocytes; Flow cytometry; Immunophenotyping; průtoková cytometrie; eutanazie u zvířat; imunofenotypizace; nádory jater; psi; Euthanasia, Animal; Next-generation sequencing; imunohistochemie; PCR for antigen receptor gene rearrangements; Dogs; Immunocytochemistry; T-lymfocyty; TCRBL; mužské pohlaví; Lymphocyte Subsets; Dog Diseases; Canine; Lymphoma, Large B-Cell, Diffuse; Ascites; Clonality; Flow Cytometry; Immunohistochemistry; nemoci psů; zvířata; Antigens, CD; CD antigeny; Neoplasia; Male; Animals